Effect of iron on microstructure and mechanical properties of primary AlSi7Mg0.3 alloy. (4th March 2017) - Sacinti, Merve; Cubuklusu, Emre; Birol, Yucel
Abstract: Effect of Fe on microstructure and mechanical properties of the primary AlSi7Mg0.3 alloy and the potential of Mn addition to counteract any adverse effects was investigated in the present work. The primary AlSi7Mg0.3 is a better alloy than its counterpart with twice as much Fe. β platelets grow twice as big when the Fe concentration is doubled. This, in turn, increases shrinkage porosity and leads to a 3-fold decrease in the tensile elongation values. Adding an equal amount of Mn helps to modify the β platelets into more compact α particles and also reduces shrinkage porosity. While these structural changes are reflected by a modest improvement in the mechanical properties, Mn addition fails to offer a full recovery in the ductility of the AlSi7Mg0.3 alloy. Hence, limiting the Fe content of the primary AlSi7Mg0.3 alloy to 0.12 wt% is worthwhile and pays off with superior microstructural features and mechanical properties.